Design And Development Of Boost A Converter Using Planar Inductor For Dual Supply Automotive System - Krishnan, Shashikumar (2008)

(untitled)
Today, innovation in electronic automobile components has resulted in the need for higher voltage power supplies. In future automotive vehicles will have 36V operating system. In order to convert to 36V operating system, a 14V/42V dual power supply design is currently being tested and implemented in electric and hybrid vehicles. In future all electrical and diesel vehicle components will be using 42V electronic components ( bulbs, alarms, radio, ICU etc). Boost converter 14V step up to 42V will be an essential component in all vehicles. This work comprises of designing an efficient boost converter which can be easily manufactured and will work for dual supply electrical vehicle as well as diesel vehicle. Current available electric vehicle converters are either buck or bidirectional type. Various topologies have been used in electric vehicle converters. In the early days, auto-transformer topology was common, followed by toroidal inductor which became popular. Currently E-I planar core with spiral PCB inductor are being gradually applied in industry. Jumpstart post embedded in the converter is another key area of electric vehicle converters with dual power supply being studied. The scopes of this research are to evaluate and experiment ideas before building and testing a design with auxiliary start (cracking) aid boost converter that would be compatible the 14V/42V power net. In this research dual supply vehicle boost converter prototype designs were experimented. The work consists of design study of CCM DC-DC Boost Converter with E-I Planar core spiral PCB inductor using a SMT UCC38C43D PWM chip controller. The experimental results are obtained using the Planar spiral inductor DC-DC boost converter, designed to operate in CCM for 120W with an efficient of 85% and output voltage ripple of 5%.